2020
DOI: 10.1177/0081246320962718
|View full text |Cite
|
Sign up to set email alerts
|

The influence of father involvement during childhood on the emotional well-being of young adult offspring: a cross-sectional survey of students at a university in Botswana

Abstract: Africa is witnessing rapid changes in family structure with noticeable absence and non-involvement of fathers in child-rearing. This study investigated the influence of father involvement in child care on the emotional well-being of young adult offspring in a cross-sectional survey of 375 students (age: M = 21.05 ± 1.94) at a university in Botswana. The Positive Affect and Negative Affect Scale and the Perception of Father Involvement Scale were used to assess emotional well-being and fathers’ involvement, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 37 publications
0
2
0
1
Order By: Relevance
“…The changes in family structure following divorce or the loss of the father could heighten the risk of the absence of an available and responsive father, deteriorating child health outcomes, including child growth and development. 22 , 23 Previous studies in the island country, the Republic of the Marshall Islands, also showed that unmarried maternal marital status was related to the risk of stunting. 24 …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The changes in family structure following divorce or the loss of the father could heighten the risk of the absence of an available and responsive father, deteriorating child health outcomes, including child growth and development. 22 , 23 Previous studies in the island country, the Republic of the Marshall Islands, also showed that unmarried maternal marital status was related to the risk of stunting. 24 …”
Section: Discussionmentioning
confidence: 98%
“…The changes in family structure following divorce or the loss of the father could heighten the risk of the absence of an available and responsive father, deteriorating child health outcomes, including child growth and development. 22,23 Previous studies in the island country, the Republic of the Marshall Islands, also showed that unmarried maternal marital status was related to the risk of stunting. 24 According to the maternal education level, children under the age of two who have mothers with any level of education were more likely than mothers without any formal education to become stunted.…”
Section: Discussionmentioning
confidence: 98%
“…The interpersonal domain includes factors like social support, emo onal support, a achment, etc. These factors may expose or prevent young people from drug and substance use [Dokkin, Civita, Paraherakis, et al, 2002;Kesebonye & Amone-P'Olak, 2021]. For instance, adolescents and young adults from situa ons with a high density of stress with less social support may be exposed to drugs and substances as a coping mechanism for the life stressors [Elliot & Lowman, 2015; Hetolang & Amone-P'Olak, 2018; Moitlakgola & Amone-P'Olak, 2015, Kga tswe & Amone-P'Olak, 2017].…”
Section: Normalisa On Theory: Developed Bymentioning
confidence: 99%
“…Дети, подвергшиеся насилию в семье, характеризуются большим количеством страхов, низким уровнем эмоциональной безопасности (Stenson, van Rooij, Carter, Powers, & Jovanovic, 2021;Масагутов и Юлдашев, 2011) и высокой эмоциональной незащищенностью (Junco-Guerrero et al, 2021). В семье, где наблюдается отсутствие участия отца в воспитании детей, чаще наблюдается эмоциональное неблагополучие ребенка (Kesebonye & Amone-P'Olak, 2021).…”
unclassified